Fertility, economic incentives and individual heterogeneity: Register data-based evidence from France and Germany - Cäcilia Lipowski; Ralf A. Wilke; Bertrand Koebel (Journal of the Royal Statistical Society: Series A (Statistics in Society), 2022)
This study demonstrates the importance of accounting for correlated unobserved heterogeneity to correctly identify the relevance of career and education for fertility decisions. By exploiting individual-level life-cycle information on fertility, career and education from large administrative longitudinal datasets, this paper shows that non-linear panel models produce substantially different results than the cross-sectional approaches widely used in previous studies. Higher opportunity costs of having children are found to be associated with lower fertility within a country, while the magnitude of the adjustment differs strongly across countries. In Germany, fertility decisions are found to depend more on individual circumstances than in France, where better public childcare support enhances the compatibility between family and professional life.
Keywords: 519; correlated random effects; family policy; Poisson panel regression; unobserved heterogeneity